Tingkat Pendapatan dan Faktor-Faktor Penentu Pendapatan UMKM di Bandar Lampung - Marlinda Apriyani; Endang Asliana; Fadila Marga Saty (Politeknik Negeri Lampung, 2016)
The existence of MSMEs is very important as either primary or additional revenue sources revenue especially for poor families. In addition, SMEs can reduce the unemployment rate. The income level of some of the home industries (IRT) in Bandar Lampung is still relatively low. The revenues earned by the business of chips, salted fish and boiled anchovies are greater than the income earned from the business of tempe, tofu and flake chips. The determinants of the level of income of MSMEs in Bandar Lampung are the level of formal education, business experience, volume of production and plans to increase production in the future.Â Keywords: MSMEs, production, income